STUDY OF THE DISTRIBUTION OF PRECIPITATION IN DISTRICT OF EASTERN MACEDONIA AND THRACE FOR THE PERIOD 1964 -1998 - Πεταλάς Χ.; Πλιάκας Φ.; Διαμαντής Ι.; Καλλιώρας Α. (Bulletin of the Geological Society of Greece, 2018)
This paper refers to the distribution and the quantitative approach of the precipitation of the Region of Eastern Macedonia and Thrace for the period 1964 - 1998 and it is based on data from 64 meteorological stations. The distribution of the precipitation varies significantly according to each different location. The mountainous terrain plays a significant role on the distribution of precipitation while the low height of precipitation is easily observed within the coastal zone. The dense forested areas are characterized by high precipitation heights and flood events. The mean precipitation for the period 1964-1998 is 660 mm. The elaboration of the rainfall data shows a distinct reduction during 1964-1998 with a drought period between 1981 and 1993. December and November are found to be the most wet months, while it is observed that 70.2% of the precipitation occurs between October and March. It is estimated that 76% to 80% of the precipitation are lower than 10 mm. The percentage of annual precipitation which outflows and/or infiltrates ranges between 23.5% to 42.5%.